DAMPAK IHTIKAR TERHADAP MEKANISME PASAR DALAM PERSPEKTIF ISLAM - Muhammad Deni Putra; Frida Amelia; Darnela Putri (Imara: JURNAL RISET EKONOMI ISLAM, 2019)
This article is intended to explore the impact of ihtikar on market mechanisms in Islamicperspective. It provides a clear conceptual description of the effects of deviant actions in the marketmechanism, namely ihtikar actions. Then the concept can be used as an analysis for the role of governmentas a regulator of the market. This research is a library research with a qualitative approach. The analysisprocess will be described using the content analysis technique. The impact arising from the practice ofihtikar is the practice of ihtikar disrupting the smooth transactions in the market, where producers gethuge profits while consumers suffer losses because producers take profits above the price they should. Thepractice of ihtikar will disrupt the market mechanism, where producers will then sell at a price higherthan the normal price. It can be assumed the practice of ihtikar in trading includes acts that are veryimmoral and also inhumane, because such trade practices create many disadvantages for human life.